Perceived discrimination in health care in Germany- results of a population survey - Olaf von dem Knesebeck; Jens Klein (BMC, 2024)
Abstract Background It has consistently been shown that perceived discrimination is associated with adverse health outcomes. Despite this uncontested relevance, there is a lack of research on the experiences of discrimination in health care. Therefore, the following research questions were addressed: (1) How often do people in Germany report having been discriminated in health care due to different reasons? (2) Which socio-demographic groups are most afflicted by perceived discrimination in health care? Methods Analyses are based on a cross-sectional online survey conducted in Germany. An adult population sample was randomly drawn from a panel which was recruited offline (N = 2,201). Respondents were asked whether they have ever been discriminated in health care due to the following reasons: age, sex/gender, racism (i.e. migration history, religion, language problems, colour of skin), health issues or disability (i.e. overweight, mental illness/addiction, disability), socio-economic status (SES, i.e. income, education, occupation). Results 26.6% of the respondents reported discrimination experiences. Perceived discrimination due to health issues or disability was most frequent (15%), followed by age (9%) and SES (8.9%). Discrimination due to racism and sex/gender was less frequently reported (4.1% and 2.5%). Younger age groups, women, and 2nd generation migrants as well as respondents with low income and low education were more likely to report any kind of discrimination in health care. Two groups were found to be at special risk for reporting discrimination in health care across different reasons: women and younger age groups. Discrimination due to racism was more prevalent among respondents who have immigrated themselves than those who were born in Germany but whose parents have immigrated. Discrimination due to SES was significantly associated with (low) income but not with education. Conclusions More than a quarter of the adult population in Germany reported experiences of discrimination in health care. Such experiences were more frequent among lower SES groups, migrants, women, and younger people. Results underline the necessity of interventions to reduce the magnitude and consequences of discrimination in health care. Future studies should apply an intersectional approach to consider interactions between social inequality indicators regarding discrimination and to identify risk groups that are potentially afflicted by multiple discrimination.